Dampak Kemampuan Bahasa Formal terhadap Penggunaan Bahasa Slang oleh Mahasiswa Prodi Pendidikan Bahasa dan Sastra Inggris Semester 1 Universitaas Muhammadiyah Maumere - Bonifasius Sepakat; Maria Gracela Leda Roga; Safilda Julita Mete; Rasmy Nurfahida; Katharina Woli Namang; Natasya Talip (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
This study aims to explore the influence of formal language skills on the use of slang among first-semester students in the English Language and Literature Education Program at Muhammadiyah University Maumere. The method used in this study is a descriptive qualitative approach with subjects consisting of first-year students. Information was collected through observation, questionnaire distribution, and brief interviews about daily language use habits and academic contexts. The findings of this study indicate that the majority of students actively use slang when interacting informally, especially when communicating with peers and on social media platforms. The use of slang serves as a way to express identity, build social solidarity, and facilitate social adjustment. However, deficiencies in formal language skills make it difficult for some students to recognize the appropriate use of language in context, so that elements of slang often creep into academic situations, such as in class discussions and assignment writing. This study concludes that formal language skills have an impact on the use of slang. Students with high formal language skills tend to be better at switching between language varieties according to context, while those with low formal skills are at greater risk of mixing them up.